Information disclosure quality and firm value: empirical evidence for an emerging integrated market (2022)
Purpose: The purpose of this study is to estimate the effect of information disclosure on firm value for firms in the Integrated Latin American Market (MILA) over the period 2011–2017. Design/methodology/approach: The study uses structural equation modeling (SEM), where the latent variable “Disclosure Quality” is measured using five textual analysis variables as indicators. The final sample is composed of 1,412 observations representing 198 firms from which we were able to collect annual reports and financial information required. Findings: The authors find a positive and statistically significant effect of “Disclosure Quality” on firm value. The indirect effect of language on firm value is also captured. Text similarity, negative tone, readability and text length in corporate disclosure are negatively related to firm value while using positive tone is positively related. In the exploratory analysis, the authors have significant effects of textual measures on disclosure quality. Originality/value: The research is original and unique as it approaches the relation between disclosure quality and market valuation of the firm using SEM for firms participating in the MILA. © 2022, Emerald Publishing Limited.